2007
DOI: 10.4049/jimmunol.179.10.6981
|View full text |Cite
|
Sign up to set email alerts
|

Altered Inflammatory Responses in TLR5-Deficient Mice Infected with Legionella pneumophila

Abstract: Legionella pneumophila (Lp), an important cause of morbidity and mortality from pneumonia, infects alveolar macrophages (AMs) and is recognized by several TLRs as well as Birc1e (NAIP5) and IL-1 converting enzyme-protease activating factor. We examined the role of TLR5 during the murine response to aerosolized Lp infection. At 4 h after infection, Tlr5−/− mice had lower numbers of polymorphonuclear neutrophils (PMNs) in their broncho-alveolar lavage fluid in comparison to wild-type (WT) mice. At 24 and 72 h, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
103
1
3

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 43 publications
8
103
1
3
Order By: Relevance
“…Because TLR5 is active when flagellin is administered i.n., we assume that apical/luminal signalling induces the epithelial response, as described previously [37]. It has been suggested that this type of epithelial innate mechanism is essential in mucosal defense against L. pneumophila, Pseudomonas aeruginosa and uropathogenic Escherichia coli [22,26,38]. Furthermore, respiratory pathogens that reach the basolateral side of the epithelial barrier via specific transport mechanisms or following trauma can stimulate either epithelial cells, airway smooth muscle, endothelial cells or any TLR5-expressing haematopoietic cells (such as lung macrophages and dendritic cells).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Because TLR5 is active when flagellin is administered i.n., we assume that apical/luminal signalling induces the epithelial response, as described previously [37]. It has been suggested that this type of epithelial innate mechanism is essential in mucosal defense against L. pneumophila, Pseudomonas aeruginosa and uropathogenic Escherichia coli [22,26,38]. Furthermore, respiratory pathogens that reach the basolateral side of the epithelial barrier via specific transport mechanisms or following trauma can stimulate either epithelial cells, airway smooth muscle, endothelial cells or any TLR5-expressing haematopoietic cells (such as lung macrophages and dendritic cells).…”
Section: Discussionmentioning
confidence: 69%
“…The matter of how epithelium and macrophages collaborate on local amplification or sequential activation of innate immunity is still under investigation. Recent observations have revealed that previous exposure to influenza virus determines the functional properties of tissueresiding macrophages in a TLR-dependent manner [38]. Whether other TLR5-expressing haematopoeitic cells like dendritic cells cooperate with epithelium also remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that TLRs contribute to the host response against L. pneumophila during in vitro and in vivo infection (Girard et al, 2003;Kikuchi et al, 2004;Akamine et al, 2005;Hawn et al, 2006Hawn et al, , 2007Fuse et al, 2007;Newton et al, 2007). However, there have been no studies to elucidate immunostimulatory properties of isolated individual proteins from L. pneumophila in terms of engagement of TLRs and linking to elicit the antigen-specific adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that TLR2 and TLR4-transmembrane pathogen recognition receptors-regulate host responses in B. pseudomallei infection in vitro and in vivo (3,4). TLR5, a sensor of bacterial flagellin, regulates host defense to a number of lung infections caused by flagellated bacteria (5)(6)(7)(8)(9). The importance of TLR5 in regulating the host response to human melioidosis has not been determined.…”
mentioning
confidence: 99%